Hypoxia Promotes a Mixed Inflammatory-Fibrotic Macrophages Phenotype in Active Sarcoidosis - Jeny, Florence; Bernaudin, Jean-François; Valeyre, Dominique; Kambouchner, Marianne; Pretolani, Marina; Nunes, Hilario; Planès, Carole; Besnard, Valérie (Frontiers in Immunology, 2021)
Background: Macrophages are pivotal cells in sarcoidosis. Monocytes-derived (MD) macrophages have recently been demonstrated to play a major role especially in pulmonary sarcoidosis. From inflammatory tissues to granulomas, they may be exposed to low oxygen tension environments. As hypoxia impact on sarcoidosis immune cells has never been addressed, we designed the present study to investigate MD-macrophages from sarcoidosis patients in this context. We hypothesized that hypoxia may induce functional changes on MD-macrophages which could have a potential impact on the course of sarcoidosis. Methods: We studied MD-macrophages, from high active sarcoidosis (AS) (n=26), low active or inactive sarcoidosis (IS) (n=24) and healthy controls (n=34) exposed 24 hours to normoxia (21% O2) or hypoxia (1.5% O2). Different macrophage functions were explored: hypoxia-inducible factor-1α (HIF-1α) and nuclear factor-kappa B (NF-B) activation, cytokines secretion, phagocytosis, CD80/CD86/HLA-DR expression, profibrotic response. Results: We observed that hypoxia, with a significantly more pronounced effect in AS compared with controls and IS, increased the HIF-1α trans-activity, promoted a proinflammatory response (TNFα, IL1ß) without activating NF-B pathway and a profibrotic response (TGFß1, PDGF-BB) with PAI-1 secretion associated with human lung fibroblast migration inhibition. These results were confirmed by immunodetection of HIF-1α and PAI-1 in granulomas observed in pulmonary biopsies from patients with sarcoidosis. Hypoxia also decreased the expression of CD80/CD86 and HLA-DR on MD-macrophages in the three groups while it did not impair phagocytosis and the expression of CD36 expression on cells in AS and IS at variance with controls. Conclusions: Hypoxia had a significant impact on MD-macrophages from sarcoidosis patients, with the strongest effect seen in patients with high active disease. Therefore, hypoxia could play a significant role in sarcoidosis pathogenesis by increasing the macrophage proinflammatory response, maintaining phagocytosis and reducing antigen presentation, leading to a deficient T cell response. In addition, hypoxia could favor fibrosis by promoting profibrotic cytokines response and by sequestering fibroblasts in the vicinity of granulomas.